Upaya Umat Kelenteng Poo An Kiong Kota Blitar dalam Menghadapi Perubahan Sosial Pasca Kebakaran: Kajian Perspektif Struktural Fungsional - Oktaviani, Firdausa Marshanda; Delijar, Ressi Maulidina (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
A Chinese temple is a sacred building used for worship and also a place to preserve Chinese ethnic culture. However, the fire disaster that befell the Poo An Kiong Temple in Blitar City had an impact on the process of carrying out worship and various other activities at the temple. This research purpose is to study how the temple devotees tries to maintain social balance when experiencing social change due to the fire that occurred at the Poo An Kiong Temple, Blitar City. The method used in this research is descriptive qualitative study. Data are collected through observation, documentation, interviews, and literature studies. The results show that temple devotees gradually move their routine activity in temple to another building in order to maintain the social balance.